Marketing Information System (Mengenali Potensi Produk pada PT. Wahana Astra Motor Cab. Pondok Pinang) - munzir munzir; tri anita (Universitas Indraprasta PGRI, 2010)
This study aims to explain the process of implementation of the Marketing InformationSystem (MkIS), especially the efforts and constraint-based constraints on information that canbe at. Astra Motor vehicle, which is located on the highway Ciputat, South Jakarta. A companythat is engaged in trading of motor vehicles, especially motorcycles Honda brand. PT. AstraMotor vehicle (Pondok Pinang) is an authorized dealer of PT. Astra International Inc., for theHonda brand vehicles, which include standard motor types, ducks types, scooter and also metictypes.Research methods used are based on survey research which described so as to produceinformation that can clarifi, the picture about the process of implementation of Marketing InformationSysterns (MkIS). Data obtained based on the observation and interviews and the literatureon computerized information systems marketing.Business developments that cause the company's advanced enough they did some adjustmentsand changes in the Marketing Information System since 2007. This change is to addresschallenges and constraints faced in the marketing field, so that the overall increase in sales onmarketing. This can be seen in sales data before and after the program Marketing InformationSystem should be applied more seriously within the company.Keywords: Marketing Information System